Apocalypse Narrative, Chaotic System: Gilbert White’s Natural History of Selborne and Modern Ecology - Scott, Heidi (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2009)
The catastrophic worldview, which has been formalized into various scientific theories (punctuated equilibrium, chaos, tipping points), covets disaster as its aesthetic, with entropy and negentropy as vying principles. At the close of the eighteenth century, science centered around the new findings of Geology, and scientists like Cuvier, Lamarck, and Buffon debated the predominance of gradual change through time versus sudden, widespread calamities or ‘punctuations.’ This essay investigates Gilbert White’s Natural History of Selborne (1789), a non-fiction, late eighteenth century natural history chronicle of a single parish through decades of close environmental observation. Its epistolary form conveys an aesthetic of discrete, close readings of nature through time, and the chronicle breaks off with the catastrophic effects of the Laki volcanic eruption of 1783. I suggest ways in which White’s famous work is unusually precocious in ecological methodology, a particularly fruitful angle because my reading goes against the perennial critical reception of Selborne as a tome of Enlightenment balance and economy. Instead, I argue that White’s work is a distinctly modern vision of catastrophic change in nature that foregrounds the contemporary science of Chaos Ecology.